The cooperation between orthodontists and surgeons in treating facial skeletal deformities - Tomaszewski, Tomasz; Baran, Marcin; Lasota, Agnieszka; Dunin-Wilczyńska, Izabella; Samczyk, Bartosz; Mitura, Iwona; Wojciechowska, Jolanta (Polish Journal of Public Health, 2015)
Face skeletal deformities have been confusing both doctors and patients for ages. The harmony of the face exerts huge influence not only on one’s psyche but also the behavior and the individual’s social and professional status. In this study we present a procedure of treating skeletal malocclusion. It was performed using various orthodontic methods, like the alteration of the growth of jaws and camouflage applied in appropriate age groups. We paid special attention to the close cooperation between the orthodontist and the surgeon, which hugely facilitates curing the most complex, multi-dimensional deformities.In this study, we present our own materials concerning the effects of cooperation between two departments of Medical University of Lublin, namely the Chair and Clinic of Maxillofacial Surgery and Department of Jaw Orthopedics.